Levels of Moral Distress, Secondary Traumatic Stress, General Health, and Empathy Among Nursing Staff in Eight Public Hospitals in Greece: A Cross‐Sectional Study. - Gamvrouli, Maria; Karanikola, Maria; Triantafyllou, Christos; Paschali, Antonia; Giannakopoulou, Margarita (Worldviews on Evidence-Based Nursing (John Wiley & Sons, Inc.), 2025)
Background: Exploring the potential relationships among moral distress (MD), general health (GH) levels, secondary traumatic stress (STS) and levels of empathy within nursing personnel is of specific interest. Aims: This study aimed to investigate the occurrence of MD and its associations with GH, STS, and empathy levels among nurses employed in eight public hospitals across the Attica Basin in Greece. Methods: Between January and March 2020, a cross‐sectional study was conducted among nursing staff working in surgical, medical, and psychiatric units of 6 public hospitals and 2 psychiatric institutions in the Attica Basin. Respondents completed the validated Greek versions of the Moral Distress Scale–Revised, the Jefferson Scale of Empathy for Health Professionals, the 28‐item General Health Questionnaire, and the Secondary Traumatic Stress Scale. Participants were asked to complete a paper‐pencil data sheet consisting of 27 sociodemographic questions. Results: A total of 267 out of 350 distributed questionnaires were completed and returned, corresponding to a response rate of 76.3%. The findings showed that nurses experienced moderate MD in both frequency and intensity, moderate‐to‐high GH and empathy, and moderate levels of STS. Psychiatric nurses reported lower STS and better GH than their counterparts in general hospital settings. Multivariate analysis demonstrated a statistically significant association between increased STS and deterioration in GH. A rise in the frequency of MD is significantly linked to an increase in its intensity. Linking Evidence to Action: Incorporating proven screening methods, programs that build resilience, supportive workplace cultures, ongoing evaluations over time, and peer support systems creates a complete approach to lowering moral distress and secondary traumatic stress, improving nurse well‐being, maintaining work efficiency, and enhancing the overall safety and quality of healthcare services.